Arsitektur Sistem Informasi Perbankan Syariah - Salsabila Firdaus; Salsa Lailatun Najwa Fillah (Cashless : Journal of Sharia Finance and Banking, 2024)
This paper examines information system architecture in the context of Islamic banking which has a unique need to comply with sharia principles. Relevant information system architecture in Islamic banking includes a comparison between centralized and distributed architecture, integration between systems such as core banking, mobile banking, and ATM, a service-oriented architecture (SOA) approach, and the application of cloud computing. Each architecture presents challenges and opportunities in implementing sharia-compliant information systems, especially in terms of data security, flexibility and cost efficiency. This article aims to provide insight into how various architectural models can support Islamic banking to achieve operational efficiency while maintaining compliance with sharia principles